2017
DOI: 10.1098/rsos.171282
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scaling behaviour and nonlinear traits in music scores

Abstract: We present a statistical analysis of music scores from different composers using detrended fluctuation analysis (DFA). We find different fluctuation profiles that correspond to distinct autocorrelation structures of the musical pieces. Further, we reveal evidence for the presence of nonlinear autocorrelations by estimating the DFA of the magnitude series, a result validated by a corresponding study of appropriate surrogate data. The amount and the character of nonlinear correlations vary from one composer to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…One attractive topic for further exploration is the scaling behavior of the rhythms observed here (He et al, 2010;Kello et al, 2010;Ville et al, 2010;Hardstone et al, 2012). Since frequency here has a novel definition, scaling behaviors would require a distinct test, a topic for future study [especially since music exhibits well-known scaling laws (Manaris et al, 2005;Lloyd, 2011;González-Espinoza et al, 2017)].…”
Section: The Music Of Thoughtmentioning
confidence: 99%
“…One attractive topic for further exploration is the scaling behavior of the rhythms observed here (He et al, 2010;Kello et al, 2010;Ville et al, 2010;Hardstone et al, 2012). Since frequency here has a novel definition, scaling behaviors would require a distinct test, a topic for future study [especially since music exhibits well-known scaling laws (Manaris et al, 2005;Lloyd, 2011;González-Espinoza et al, 2017)].…”
Section: The Music Of Thoughtmentioning
confidence: 99%
“…8 is suggestive. Note that though evidence for different profiles of nonlinear correlations in music scores has been reported previously [20], a specific index such as ξ , able to quantify the amount of nonlinearity in a signal, was lacking.…”
Section: B Nonlinearity Index ξmentioning
confidence: 91%
“…While it has been extensively certified that music evidences long-range temporal correlations with (typically) a heavy tailed power spectrum [1,3,7,8], less is known about nonlinear correlations. However, recent studies have reported evidence of nonlinear correlations in musical pieces and discussed their possible relevance in their structure [20].…”
Section: B Nonlinearity Index ξmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses based on statistical methods can capture information about musical features, such as the style of a musical piece, the composer, and even the emotions conveyed [1,[3][4][5][6][7][8][9][12][13][14][15][16][17][18][19][20]. Several statistical analyses employ successive pitches as units of context.…”
Section: Introductionmentioning
confidence: 99%